Catalytic β-Bromohydroxylation of Natural Terpenes: Useful Intermediates for the Synthesis of Terpenic Epoxides. (23rd January 2019) - Oubaassine, Saadia; Köckritz, Angela; Eckelt, Reinhard; Martin, Andreas; Ait Ali, Mustapha; El Firdoussi, Larbi
Abstract : In a one-step procedure, various β -bromoalcohols were synthesized from natural terpenes in good to excellent yields. Using different catalysts, the reaction was carried out at room temperature, with H2 O as nucleophile and N -bromosuccinimide as a bromine source under mild reaction conditions. The synthesized β -bromoalcohols were subsequently converted in situ to the corresponding epoxides in good yields.